REKONSTRUKSI KERANGKA HUKUM PERLINDUNGAN KONSUMEN DALAM EKOSISTEM PLATFORM DIGITAL DI INDONESIA - Ardenolis; Najla'a Talitha Kadisai; Melioner Permata Rahman (Komunitas Manajemen Kompetitif, 2026)
The development of the digital platform ecosystem in Indonesia has created significant normative gaps in the existing consumer protection legal framework. Law Number 8 of 1999 on Consumer Protection, as the primary legal instrument, has proven inadequate in accommodating the complexity of legal relationships among consumers, businesses, and digital platforms in the digital economy era. This research aims to analyze the structural weaknesses of the existing consumer protection legal framework, identify regulatory gaps in the digital platform ecosystem context, and reconstruct a legal framework responsive to digital dynamics. The research methodology employs a normative juridical approach with statutory, conceptual, and comparative methods. The results reveal at least three fundamental regulatory gaps: the ambiguity of digital platform legal liability, weaknesses in digital dispute resolution mechanisms, and insufficient protection of consumer personal data. The proposed legal framework reconstruction encompasses strengthening the platform's position as an independent legal subject, integrating strict liability principles in digital transactions, and establishing an integrated supervisory authority. This research contributes to the development of an adaptive and comprehensive digital consumer protection law in Indonesia.